2011
DOI: 10.1073/pnas.1017431108
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri -produced cyclic dipeptides quench agr -mediated expression of toxic shock syndrome toxin-1 in staphylococci

Abstract: The production of the staphylococcal exotoxin toxic shock syndrome toxin-1 (TSST-1) by Staphylococcus aureus has been associated with essentially all cases of menstruation-associated toxic shock syndrome (TSS). In this work, we show that the human vaginal isolate Lactobacillus reuteri RC-14 produces small signaling molecules that are able to interfere with the staphylococcal quorum-sensing system agr, a key regulator of virulence genes, and repress the expression of TSST-1 in S. aureus MN8, a prototype of mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
144
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(153 citation statements)
references
References 50 publications
(54 reference statements)
2
144
0
Order By: Relevance
“…Although mutation of the repressor of toxins (rot) transcriptional regulator was reported to have little effect on TSST-1 expression, overexpression of Rot in trans strongly repressed TSST-1 (15). In addition to these experiments, prior work from our laboratory has demonstrated that interspecies communication between Lactobacillus reuteri and S. aureus can result in a dramatic repression of TSST-1 expression (18). Although this phenotype correlated with repression of agr, and deletion of agr in S. aureus MN8 reduced TSST-1 expression, TSST-1 could be further repressed in the agr-null background by the L. reuteri signaling molecules.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Although mutation of the repressor of toxins (rot) transcriptional regulator was reported to have little effect on TSST-1 expression, overexpression of Rot in trans strongly repressed TSST-1 (15). In addition to these experiments, prior work from our laboratory has demonstrated that interspecies communication between Lactobacillus reuteri and S. aureus can result in a dramatic repression of TSST-1 expression (18). Although this phenotype correlated with repression of agr, and deletion of agr in S. aureus MN8 reduced TSST-1 expression, TSST-1 could be further repressed in the agr-null background by the L. reuteri signaling molecules.…”
mentioning
confidence: 87%
“…The tst gene promoter (P tst ) was previously cloned into the luciferase reporter plasmid pAmilux (18,24). The pAmilux::P tst plasmid was transformed into the different MN8 clones.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stereochemistry of the compounds play an important role in biological activity. Li et al 49 reported the production of two stereoisomeric CDPs, cyclo(L-Tyr-L-Pro) and cyclo(L-Tyr-D-Pro) from Lactobacillus reuteri, where cyclo(L-Tyr-L-Pro) is more effective against S. aureus which causes menstruation-associated toxic shock syndrome (TSS) in human.…”
Section: Discussionmentioning
confidence: 99%